PENGEMBANGAN PRODUK TORTILLA DENGAN KOMBINASI TEPUNG JAGUNG, LABU KUNING DAN TEMPE - Syirril Ihromi; Dina Putri; Marianah Marianah; Nurhayati Nurhayati (Fakultas Teknologi Pangan dan Agroindustri, Universitas Mataram, 2022)
Tortilla is a product that uses corn flour as the basic ingredient and is made through the process of cooking, grinding, drying, and frying. Pure corn-based tortillas are high in carbohydrates but low in protein. This study aims to find the best combination formula between corn, pumpkin, and tempe flour, and to determine the effect of the combination formula on chemical and organoleptic properties. The data were analyzed using an experimental design, namely Completely Randomized Design with one factor: a combination of hybrid corn flour, pumpkin and tempe formulas, treatment 1 (50% corn flour, 0% pumpkin flour: 50% tempe flour), 2 (50% corn flour, 10% pumpkin flour: 40% tempe flour), 3 (50% corn flour, 20% pumpkin flour: 30% tempe flour), 4 (50% corn flour, 30% pumpkin flour: 20% tempe flour), 5 (50% corn flour, 40% pumpkin flour : 10% tempe flour) and 6 (50% corn flour, 50% pumpkin flour: 0% tempe flour). The results of the analysis obtained were continued with the Honest Significant Difference test at the 5% level. The parameters observed were water content, ash content, fiber content, protein content, and organoleptic tests (color, aroma, texture, and taste). From chemical and organoleptic properties, the best treatment was found in the T2 treatment with a moisture content of 11.03%, ash content of 3.39%, fiber content of 11. 25%, and protein content of 12.88%, with the slightly brown color of tortillas, slightly like the aroma (the typical aroma of tempe), slightly good taste, and the texture is slightly crunchy.